ChemInform Abstract: Chirality Transfers Through Sequential Sigmatropic Rearrangements of Allylic Vicinal Diols: Development and Application to Total Synthesis of (‐)‐Kainic Acid. Issue 2 (9th January 2013) - Kitamoto, Katsunori; Nakayama, Yasuaki; Sampei, Mana; Ichiki, Masato; Furuya, Naoya; Sato, Takaaki; Chida, Noritaka
Abstract Starting from enantiopure allylic vicinal diols, Claisen/Claisen rearrangements install two identical functional groups while sequential Claisen/Overman rearrangements install two different functional groups.